Radiology technologists in the humanization process of mammography exam - Moreira Souza Prado, Amanda; Gonçalves de Souza, Andressa; Henrique de Jesus da Silva, Pedro; Borges Martins de Castro, Waldemar; do Socorro Lima Silva, Maria; de Sena Mendes Silva, Dhaiane; Lucia Teodoro dos Santos Souza, Vera (Seven Editora, 2023)
Introduction: Humanized care prioritizes dialogue and patient needs, and the trust generated between patients and professionals contributes to the effectiveness of better care in the mammography exam. Objective: This article aims to discuss the process of humanization of the professional radiological techniques that work in mammography and how this positively affects the female audience during the examination. Materials and Methods: are presented as a literature review, in which it seeks an approach to causes and conflicts, described by the selected community. Results: An increase in the mortality rate of breast cancer in women is observed over some time, combined with the complaint of the lack of welcoming care by the technologist during mammography. Discussion: Therefore, it is argued that for a professional to be excellent in his area of expertise, in addition to his ability to perform quality exams, it is as important as going through the humanization process. Conclusion: it is known that the practice of humanized care aims to guarantee human needs, through dedication and teamwork, ensuring self-care, recovery, maintenance, and health promotion together. DOI: https://doi.org/10.56238/devopinterscie-118